PENINGKATAN PEMAHAMAN MASYARAKAT TENTANG PENYAKIT DEMAM BERDARAH (DBD) MELALUI TINDAKAN PERILAKU HIDUP BERSIH DAN SEHAT - winnellia fridina sandy rangkuti (Universitas Muhammadiyah Klaten, 2026)
Dengue Haemorrhagic Fever (DHF), also known as dengue haemorrhagic fever (DHF), is a disease caused by the dengue virus, transmitted by the Aedes aegypti mosquito through bites. Dengue haemorrhagic fever is a highly lethal disease. It can affect people of all ages, especially children (Ministry of Health, 2017). The increase in DHF cases every year is greatly influenced by the behavior of the community, which often fails to adopt healthy lifestyles both at home and at school, allowing the Aedes aegypti mosquito to thrive and reproduce. Purpose: This activity aims to provide education on clean and healthy lifestyles to prevent and control DHF. Method: The activity involves explanations about the disease and efforts that can be made to prevent and control it, followed by discussions and question-and-answer sessions. Results: The education shows that there is an understanding among the community about disease control and the efforts that can be made, as well as an understanding of the signs and symptoms experienced when infected and actions that can be taken independently when encountering early symptoms of DHF.